Metode Pengumpulan Data Debit Air Pada Saluran Distribusi Air PDAM Makassar Berbasis IoT - Andi Imran; Nurul Azizah; Satria Gunawan Zain; Zulhajji; Dwi Ajiatmo (Universitas Darul Ulum, 2024)
Water is an important resource for human survival as well as various economic sectors. PDAM is responsible for providing water supply to the community. One of the major challenges faced in managing water supply is the problem of water loss or leakage. This research aims to overcome this problem by designing an innovative method to collect water discharge data on the distribution channel of PDAM Makassar using Internet of Things (IoT) technology. This method uses the ESP32-CAM to take images of the water meter on the main pipe and save it to a database. Optical Character Recognition (OCR) technology is used to convert the image into text that can be processed. The test results show that the average error in meter readings is 0.215% with an average accuracy rate of 98%. Overall the system works well in reading digital meters and is reliable in monitoring water consumption visually and in real-time. Thus, this method can be an effective solution in detecting water leaks and improving the efficiency of water supply management by PDAMs, as well as saving resources and operational costs.